The Effects of Irrigation and Climate on the High Plains Aquifer: A County‐Level Econometric Analysis. (14th August 2019) - Silva, Felipe; Fulginiti, Lilyan; Perrin, Richard; Schoengold, Karina
Abstract: The High Plains Aquifer (HPA) underlies parts of eight states and 208 counties in the central area of the United States (U.S.). This region produces more than 9% of U.S. crops sales and relies on the aquifer for irrigation. However, these withdrawals have diminished the stock of water in the aquifer. In this paper, we investigate the aggregate county‐level effect on the HPA of groundwater withdrawal for irrigation, of climate variables, and of energy price changes. We merge economic theory and hydrological characteristics to jointly estimate equations describing irrigation behavior and a generalized water balance equation for the HPA. Our simple water balance model predicts, at average values for irrigation and precipitation, an HPA‐wide average decrease in the groundwater table of 0.47 feet per year, compared to 0.48 feet per year observed on average across the HPA during this 1985–2005 period. The observed distribution and predicted change across counties is in the (−3.22, 1.59) and (−2.24, 0.60) feet per year range, respectively. The estimated impact of irrigation is to decrease the water table by an average of 1.24 feet per year, whereas rainfall recharges the level by an average of 0.76 feet per year. Relative to the past several decades, if groundwater use is unconstrained, groundwater depletion would increase 50% in a scenario where precipitation falls by 25% and the number of degree days above 36°C doubles. Editor's note : This paper is part of the featured series on Optimizing Ogallala Aquifer Water Use to Sustain Food Systems. See the February 2019 issue for the introduction and background to the series. Abstract : Research Impact Statement : Results show the average net effect of irrigation in the High Plains Aquifer is a reduction in groundwater level of 0.47 feet per year. Climate change could significantly increase the rate of change.